MATHEMATICAL LATERAL THINKING OBSTACLES IN SOLVING GEOMETRIC PROBLEMS BASED ON BRAIN DOMINANCE - Lukman Jakfar Shodiq; Dwi Juniati; Susanah Susanah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Creative thinking was characterized by the emergence of new ideas which was an important skill for students. Lateral thinking was one way to grow new ideas. Generally, related research was carried out to see the thinking process and its level only with the results of the majority of low levels (especially in geometry problems), so further research was needed to find out what were the obstacles. This study aims to find mathematical lateral thinking barriers based on brain dominance. This research was a qualitative research with a case study approach. The instruments were a brain dominance test, creativity questions, and geometry questions for lateral thinking. Triangulation of data collection techniques was carried out To ensure data validity. Obtained two main subjects LCS and RCS. Analysis of subjects' answers, interview and observations transcripts were carried out by coding the inhibiting factors then analyzed by Toulmin's arguments analysis. We findings that left-brain dominant student experience ontogenic barriers in finding something new caused bounded by concepts and right-brain dominant student experience epistemological barriers in finding different ways cause bounded by context. Further research was needed with students who have high mathematical abilities and creativity to find out how to overcome lateral thinking obstacles.